New-onset diabetes mellitus type 2 treated with metformin - is it possible to slow the development of pancreatic cancer?- case report: New-onset DM2 and pancreatic cancer treated with metformin - Pochodowicz, Katarzyna; Rogowska , Karolina; Zawistowska , Julia; Rutkowska-Kawalec, Weronika; Kawalec , Jakub; Lęgas, Angelina; Smalira , Joanna; Rogala, Weronika; Przybysz , Bartosz; Urbańska, Karolina (Quality in Sport, 2024)
In this article, we present the case of an 87-year-old patient whose initial symptom of developing pancreatic cancer was newly diagnosed type 2 diabetes mellitus. She was treated with metformin, which, on the one hand, could slow the development of pancreatic cancer and, on the other hand, delayed a key cancer diagnosis. However, before the definitive diagnosis, the patient’s symptoms were considered merely as side effects of metformin treatment, delaying the proper diagnosis. We consider that early diagnosis of pancreatic cancer remains a significant challenge. Often, the first symptom is newly diagnosed diabetes mellitus type 2. In this article, we aim to demonstrate the importance of being vigilant when diagnosing and treating diabetes mellitus with metformin. We also present the impact of metformin on the course of pancreatic cancer. Additionally, we emphasize the need to be attentive when patients complain of side effects of this medication, as they may often mask the development of pancreatic cancer.